Description of the zoeal stages of Periclimenes aegylios Grippa & d’Udekem d’Acoz, 1996 (Crustacea: Decapoda: Palaemonidae) reared in the laboratory - Muzio, Giorgia Di; Basile, Rita; Pessani, Daniela (Zootaxa, 2018)
The eight zoeal stages of the Mediterranean shrimp Periclimenes aegylios are described and illustrated in detail, using laboratory-reared specimens. This study improved the partial and unpublished descriptions of the zoeae of this species. The complete and accurate definition of the morphology of all the stages now allows comparison of the zoeae of P. aegylios with those of other Mediterranean Periclimenes species, as well as the allopatric Atlantic P. sagittifer, from which P. aegylios was separated in 1996.